Multisystem inflammatory syndrome in children: A case report from India - Satya Prakash; Banothu Kiran Kumar; Tanima Dwivedi; Jhuma Sankar (Wolters Kluwer Medknow Publications, 2020)
With reports of a multisystem inflammatory syndrome in children (MIS-C) related to COVID-19 infection resembling Kawasaki disease, there is an increasing need for awareness of this condition, especially in resource-limited settings. Herein, we report a 6-year-old previously healthy boy, who presented with a short history of fever, rash, and difficulty in breathing. At admission, he had bilateral nonexudative conjunctival congestion, oral erythema, maculopapular rash, and hemodynamic instability. Investigations showed neutrophilic leukocytosis, elevated inflammatory markers, and cardiac dysfunction. The child was managed with invasive ventilatory support, vasoactive agents, and broad-spectrum antibiotics and was given intravenous immunoglobulins and steroids. Reverse transcription-polymerase chain reaction for SARS-CoV-2 was negative; however, antibody test for SARS-CoV-2 was positive, confirming the diagnosis of MIS-C. The child improved clinically, inflammatory markers decreased, and the child could be discharged after 10 days of hospital stay.